Transplanting and the addition of boron in sweet corn (Zea mays L. group saccharate) production = Trasplante y adición de boro en la producción de maíz dulce (Zeamays L. grupo saccharate) - Al Shammari, Aziz Mahdi Abd
Introduction. Low seedbed temperatures at the planting and the direct sowing method can reduce the sweet corn germination. Transplanting may offer optimum environmental conditions for seed germination, early crop maturity, and increase sweet corn (Zea mays L. group saccharata) productivity. Boron deficiency depresses sweet corn yield through male sterility. Objective. To evaluate the effect of transplanting and the addition of boron in sweet corn production. Materials and methods. A field experiment was conducted from March 19 to June 20, 2020 at the Research Station of Horticulture Department and Landscape Gardening Architecture, University of Diyala, Baqubah, Iraq. Direct sowing and transplanting, and foliar application of boron at 0, 50, or 75 mg L-1 was evaluated to determine effects on the yield, the yield components, and water use efficiency of sweet corn cultivars: Roi Soleal, Seker misir, and Succar. Results. The cv. Seker Misir matured faster (57.5 days), had wider ears (4.53 cm), more kernel rows (16.0), the highest kernel yield (6.00 t ha-1), and a higher water use efficiency (WUE) (2.85 kg m-3). The cv. Succar had the longest ears (18.48 cm) and the heaviest fresh ears (251 g). Transplanting hastened the time to maturity (54.18 days), and produced the longest ears (17.91 cm), widest ears (4.52 cm), most kernel rows (15.96), heaviest fresh ears (229 g), the highest kernel yield (5.56 t ha-1), and the highest WUE (2.64 kg m-3). The 50 mg L-1 fertilizer treatment produced the longest ears (17.61 cm), widest ears (4.58 cm), more kernel rows (16.61), the highest kernel yield (5.64 t ha-1), and the highest WUE (2.68 kg m-3). The least time to maturity (57.72 days) and heaviest fresh ears (232 g) occurred with 75 mg L-1 of boron fertilizer. Conclusion. The use of 50 mg L-1 boron, as a foliar fertilizer, appears to be, next to the transplanting method, suitable for the cultivation of sweet corn plants to increase productivity and WUE.